Myocardin-Related Transcription Factor A Is a Common Mediator of Mechanical Stress- and Neurohumoral Stimulation-Induced Cardiac Hypertrophic Signaling Leading to Activation of Brain Natriuretic Peptide Gene Expression - Kuwahara, Koichiro (American Society for Microbiology (ASM), 2010)
Subjecting cardiomyocytes to mechanical stress or neurohumoral stimulation causes cardiac hypertrophy characterized in part by reactivation of the fetal cardiac gene program. Here we demonstrate a new common mechanism by which these stimuli are transduced to a signal activating the hypertrophic gene program. Mechanically stretching cardiomyocytes induced nuclear accumulation of myocardin-related transcription factor A (MRTF-A), a coactivator of serum response factor (SRF), in a Rho- and actin dynamics-dependent manner. Expression of brain natriuretic peptide (BNP) and other SRF-dependent fetal cardiac genes in response to acute mechanical stress was blunted in mice lacking MRTF-A. Hypertrophic responses to chronic pressure overload were also significantly attenuated in mice lacking MRTF-A. Mutation of a newly identified, conserved and functional SRF-binding site within the BNP promoter, or knockdown of MRTF-A, reduced the responsiveness of the BNP promoter to mechanical stretch. Nuclear translocation of MRTF-A was also involved in endothelin-1- and angiotensin-II-induced activation of the BNP promoter. Moreover, mice lacking MRTF-A showed significantly weaker hypertrophic responses to chronic angiotensin II infusion than wild-type mice. Collectively, these findings point to nuclear translocation of MRTF-A as a novel signaling mechanism mediating both mechanical stretch- and neurohumoral stimulation-induced BNP gene expression and hypertrophic responses in cardiac myocytes.